2002
DOI: 10.1046/j.1083-4389.2002.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin‐Tetracycline Combinations are Inadequate as Alternative Therapies for Helicobacter pylori Infection

Abstract: Although the amoxicillin/tetracycline combination is attractive (inexpensive, safe, and with low primary resistance rate), it can not be recommended for H. pylori eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 23 publications
(30 reference statements)
0
36
0
Order By: Relevance
“…Eleven of the studies were multicentre RCTs [15,21,25,29,31,32,34,39,41,44,45] . Duration of bismuth therapy ranged from 7 to 56 d, with a total daily dose of between 400 mg and 2100 mg. Nineteen studies used ranitidine bismuth citrate [15,17,20,22,24,[28][29][30][31][32]34,36,[39][40][41]43,45,46,48] , ten studies colloidal bismuth subcitrate [7,16,18,21,26,27,37,38,42,44] , two studies tripotassium dictrato bismuthate [23,35] , two studies bismuth subsalicylate [25,33] , one study bismuth subnitrate [19] , and one study both bismuth subnitrate and www.wjgnet.com…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven of the studies were multicentre RCTs [15,21,25,29,31,32,34,39,41,44,45] . Duration of bismuth therapy ranged from 7 to 56 d, with a total daily dose of between 400 mg and 2100 mg. Nineteen studies used ranitidine bismuth citrate [15,17,20,22,24,[28][29][30][31][32]34,36,[39][40][41]43,45,46,48] , ten studies colloidal bismuth subcitrate [7,16,18,21,26,27,37,38,42,44] , two studies tripotassium dictrato bismuthate [23,35] , two studies bismuth subsalicylate [25,33] , one study bismuth subnitrate [19] , and one study both bismuth subnitrate and www.wjgnet.com…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…Ten of the studies reported the method of generation of the randomization schedule [15,18,20,26,30,32,37,39,47,48] , but only four the method of concealment of allocation [27,32,47,48] . Four of the studies recorded adverse events using a questionnaire [20,24,28,40] , but only two of these stated that the questionnaire was validated [24,28] . Seven studies collected information concerning adverse events using a diary or diary cards [21,27,32,[34][35][36]48] , two via face-toface interview [43,45] , and one via telephone interview [46] .…”
Section: Trial Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…14 In a study comparing arms with tetracycline and doxycycline, both arms had similar eradication rates. 15 The main difference in antimicrobial resistance between the two drugs is that doxycycline can inhibit some tetracycline resistant Gram-positive bacteria. 16 Results suggest similar eradication rates, but there was significantly better compliance with doxycycline.…”
Section: Discussionmentioning
confidence: 99%